A Randomized, Double-Blind, Single-Dose Study Comparing the Biosimilarity of HOT-1010 With Bevacizumab (Avastin®) in Chinese Healthy Male Subjects - Huang, Kai; Que, Linling; Ding, Ying; Chu, Nannan; Qian, Zhenzhong; Shi, Yunfei; Qin, Wei; Li, Zhenni; Chen, Yuanxin; Gu, Xianghong; Wang, Jiakun; Zhang, Lin; et al. (Frontiers in Pharmacology, 2021)
Objective: This study was conducted to compare the pharmacokinetics, safety and immunogenicity of HOT-1010 with bevacizumab (Avastin®) in Chinese healthy male subjects. Methods: A single-center, randomized, double-blind, single-dose, parallel trial was performed in 84 Chinese healthy male subjects who randomly (1:1) received a single intravenous infusion of 1 mg/kg HOT-1010 or Avastin® for 90 mins and followed up for 85 days. Serum concentrations of bevacizumab were analyzed by enzyme-linked immunosorbent assay. Primary pharmacokinetic (PK) parameters, Cmax, AUC0-t and AUC0-∞, were calculated and evaluated the bioequivalence between HOT-1010 and Avastin®, the safety and immunogenicity of investigational drugs were also assessed. Results: A total of 82 subjects completed the study. The 90% Confidence Intervals (CIs) for geometric mean ratios (GMRs) of Cmax, AUC0-t and AUC0-∞ were 91.81-103.64%, 85.19-95.39% and 85.04-95.36%, which were all within the bioequivalence margin. Treatment-emergent adverse events (TEAEs) were reported in 27 (65.9%) subjects in HOT-1010 group and 23 (56.1%) subjects in Avastin® group. Most TEAEs were mild or moderate. No TEAEs, Serious Adverse Events (SAEs) or deaths leading to discontinuation was reported. Subjects were all tested negative for Anti-drug Antibody (ADA). Conclusion: HOT-1010 exhibited the similar pharmacokinetics, safety and immunogenicity profiles of bevacizumab (Avastin®) in Chinese healthy male subjects.